Las memorias ficcionalizadas de J. M. Coetzee: Boyhood, Youth y Summertime - Antón-Pacheco Sánchez, Luisa (Epos : Revista de filología, 2013)
El artículo analiza Boyhood, Youth y Summertime, las memorias ficcionalizadas de Coetzee, recogidas en un solo volumen con el título Scenes from Provincial Life. Se estudian las características formales, preocupaciones temáticas y rasgos más significativos de cada obra, así como la manera en que se presentan retratos del artista en distintas etapas y contextos. Se estudia la relación de la trilogía con el conjunto de la obra de Coetzee. También se analiza la forma en que Coetzee diluye las fronteras entre géneros y nos hace reflexionar sobre las convenciones de los géneros autobiográficos y las distintas técnicas para narrar la vida. The article analyses Boyhood, Youth and Summertime, Coetzee´s fictionalized memoirs, later published in one volume entitled Scenes from Provincial Life. The article focusses on the formal characteristics, thematic concerns and significant features of each work and analyses the portraits of the artist which emerge. It traces the way the artist is presented in different contexts at different times. The article also examines the relationship between certain aspects of the trilogy and other works by Coetzee. It analyses the way Coetzee blurs the boundaries between genres and makes us reflect on the conventions of autobiographical narratives and on the different techniques that can be used in life-writing.